Teaching Mathematics in Financial Institutes - Hakim Murtazakulovich Xudoyberdiev (Open Academia, 2023)
Mathematics as an academic subject contains the necessary prerequisites for the development of students' cognitive abilities, it forms and corrects such forms of thinking as synthesis, comparison, analysis, develops the ability to generalize to concretize, creates conditions for correcting memory, attention and other mental functions. In this process, the development of children's speech is observed, it is enriched with special mathematical terms and expressions.